2012
DOI: 10.1016/j.ophtha.2012.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Volume Variations with Age, Axial Length, and Sex in Healthy Subjects: A Three-Dimensional Analysis

Abstract: Purpose To demonstrate the three-dimensional choroidal volume distribution in healthy subjects using enhanced depth imaging (EDI) spectral-domain optical coherence tomography (SD-OCT) and to evaluate its association with age, sex, and axial length. Design Retrospective case series. Participants One hundred and seventy six eyes from 114 subjects with no retinal or choroidal disease. Methods EDI SD-OCT imaging studies for healthy patients who had undergone a 31-raster scanning protocol on a commercial SD-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
133
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 41 publications
20
133
3
1
Order By: Relevance
“…In adults over a mean age of 45 years old, Hirata et al 9 found a total volume of 5.411±2.097 mm 3 (mean age 65 years); Shin et al 28 reported a total volume of 7.72±1.2 mm 3 (mean age M A N U S C R I P T , respectively. Differences in choroidal volume between the sexes were reported by these same authors, 29 with the values for males being 7.37% greater than those for females. We found similar total volumes for both females and males, as shown in Table 4, with no significant differences in certain areas.…”
Section: Discussionmentioning
confidence: 69%
“…In adults over a mean age of 45 years old, Hirata et al 9 found a total volume of 5.411±2.097 mm 3 (mean age 65 years); Shin et al 28 reported a total volume of 7.72±1.2 mm 3 (mean age M A N U S C R I P T , respectively. Differences in choroidal volume between the sexes were reported by these same authors, 29 with the values for males being 7.37% greater than those for females. We found similar total volumes for both females and males, as shown in Table 4, with no significant differences in certain areas.…”
Section: Discussionmentioning
confidence: 69%
“…Li et al 26 reported that choroidal thickness was 18% higher in men than in women in young adults. Barteselli et al 30 measured the choroidal volume and reported that men had significantly higher choroidal volume than women. As the relationship between age and SFCT, the association between sex and SFCT in our study population was relatively weak with a standardized correlation coefficient b of À0.07 and a P value of 0.04 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology adopted in this work-measurement of CT at 9 points per eye-aims to reduce this error. However, the measurement of choroidal volume 55 or the development of automatic software would certainly be better ways to study its anatomy.…”
Section: Discussionmentioning
confidence: 99%